Correlation of amniotic fluid inflammatory markers with preterm birth: a meta-analysis - Cong Wang; Qin Chen; Yan Wang (Journal of Obstetrics and Gynaecology)
Background The relationship between amniotic fluid inflammatory biomarkers and preterm birth in second- or third-trimester pregnancy has been a focus, and understanding the correlation between these markers and preterm birth is important for early identification and intervention in preterm birth. The aim of this study was to explore potential inflammatory biomarkers in second- or third-trimester pregnancy amniotic fluid associated with preterm birth.Methods On November 30, 2023, we searched literature involved the influence of second- or third-trimester pregnancy amniotic fluid inflammatory biomarkers on preterm birth through PubMed, Web of Science, Embase, Scope, CNKI, WanFang, VIP and China Biomedical Databases. The search languages were Chinese and English. Included outcomes indexes were combined utility analysis via R software.Results A total of 11 articles were included in the combined utility analysis. This combined analysis revealed significant differences in several inflammatory biomarkers in amniotic fluid between the two groups (MD = 6.87, 95%CI: 0.26 − 13.47, P < 0.01); the difference in amniotic fluid IL-6 between the two groups (MD = 5.73, 95%CI: 3.13–8.32, P < 0.01); the difference in amniotic fluid IL-10 between the two groups (MD = 0.11, 95%CI: −3.26–3.48, P < 0.01); the difference in amniotic fluid CRP between the two groups (MD = 21.34, 95%CI: 11.69–30.89, P < 0.01); the difference in amniotic fluid MCP-1 between the two groups (MD = 312.14, 95%CI: 211.34–412.97, P < 0.01); the difference in the amniotic fluid MMP-9 between the two groups (MD = 0.86, 95%CI: −0.10–1.82, P < 0.01); and the difference in TNF-α in amniotic fluid between the two groups (MD = 22.78, 95%CI: −5.05–50.61, P < 0.01).Conclusions The inflammatory biomarkers IL-1β, IL-6, IL-10, CRP, TNFα, MCP-1 and MMP-9 in the amniotic fluid of patients in the second- or third-trimester pregnancy were all correlated with preterm birth.